Fabrication and characterisation of suspended microstructures of tantalum. (16th November 2016) - Al-masha'al, A; Mastropaolo, E; Bunting, A; Dunare, C; Cheung, R
Abstract: An investigation of the influence of deposition and post-fabrication processes on the final mechanical structure of tantalum beams is reported in the present study. The final deflection profiles of doubly supported beams made from compressive and tensile-stressed films have been studied experimentally. An optimum finite element model has been developed to predict the buckling behaviour of the doubly supported beams by considering the boundary conditions in the form of a compressive stress and an applied load. No matter which etch release method has been used, the initial stress state of the as-deposited films has been found to have a significant impact on the final deflection profile of the fabricated device. The compressive-stressed films have presented larger deflection in the final released beams than the tensile-stressed films. Taking into account the type of etch release methods, the beams that have been released in the dry etch release processes have been found to deform more vertically than those released in the wet-etch release method. Moreover, it has been found that the amplitude of vertical deflection increases with the increase of the beam length and thickness. The results indicate that optimum profiles of tantalum suspended structures can be obtained from the tensile-stressed films that have been released by the wet etching method with an aspect ratio of 1:48.